Assessing heat stress tolerance in Castanea sativa. (2nd July 2022) - Dorado, F Javier; Solla, Alejandro; Alcaide, Francisco; Martín, M Ángela
Abstract: Increasing temperatures and heat waves decimate the productivity and survival of valuable trees like the European chestnut ( Castanea sativa Miller). The main objectives of this study were to assess variation in heat stress tolerance within and between chestnut populations, select molecular markers associated with heat stress tolerance, and to use the selected markers to explore the adaptive potential of C. sativa to tolerate heat stress. Forty-eight trees from three Spanish wild chestnut populations of contrasting climate characteristics were used. Seven out of 20 expressed sequence tag- simple sequence repeat (EST-SSR) markers were selected. To validate the markers, progenies of the 48 trees were subjected to heat stress for 7 days and their heat tolerance was assessed through morphological and physiological changes. Leaf proline content induced by heat was highest in the least thermophilic population. Genetic structure analysis of populations revealed a cluster that included 81 per cent of the seedlings of the most thermophilic population. Signatures of positive selection for heat stress tolerance were detected using VIT099 and POR016 markers, associated with the antioxidant response of plants to heat damage. These markers should be included as candidates for their use in early selection of individuals tolerant to heat stress in C. sativa . Molecular and physiological findings converged in this study to better understand chestnut adaptation to global warming.